Terahertz Dating of Sedimentary Rocks - Meng, Zhaohui; Zhan, Honglei; Chen, Ru; Miao, Xinyang; Zhao, Kun (Frontiers in Physics, 2022)
The depositional products of sedimentary rocks provide vital references for investigating the paleoenvironment, paleogeography, and tectonic evolution history. However, the detection methods of geological evolution are still relatively complicated, and how to combine geological age and geological evolution is confusing. Based on the sensitivity of terahertz waves to organic matter, a THz dating method was introduced for characterizing the geological age of sedimentary rocks. In this study, the geological evolution of Liujiang Basin was analyzed by using terahertz time domain spectroscopy (THz-TDS). According to the close relation between organic matter content and sedimentary environment, it can be inferred that the geological deposition in this area is affected by Marine cover. In addition, the refractive index of Ordovician sedimentary rocks is significantly higher than that of other sedimentary rocks. Based on these results, it is inferred that the sedimentary environment of the Liujiang Basin gradually changed from continental deposition to deep-water marine deposition from the Neoproterozoic to the Ordovician, and the sea water gradually retreated due to the crustal movement, resulting in a transition from deep-water deposition to continental inshore ocean facies deposition. These findings are highly consistent with the geological history of the study area. Combined with principal component analysis (PCA) technology, the relative geological age of sedimentary rocks can be divided. Our study con-firmed the reliability of this THz dating technique, which provides an effective way to study the geological evolution history of sedimentary rocks.